A chronicle review of new techniques that facilitate the understanding and development of optimal individualized therapeutic strategies for chordoma - Zhao, Chenglong; Tan, Tao; Zhang, E.; Wang, Ting; Gong, Haiyi; Jia, Qi; Liu, Tielong; Yang, Xinghai; Zhao, Jian; Wu, Zhipeng; Wei, Haifeng; Xiao, Jianru; et al. (Frontiers in Oncology, 2022)
Chordoma is a rare malignant bone tumor mainly occurring in the sacrum and the clivus/skull base. Surgical resection is the choice of treatment for chordoma, but the local recurrence rate is high with unsatisfactory prognosis. Compared with other common tumors, there is not much research and individualize treatment for chordoma, partly due to the rarity of the disease and a lack of appropriate disease models, which procrastinate the discovery of therapeutic strategies. Recent advances in modern techniques have enabled us to gain a better understanding about some rare diseases such as chordoma. Since the beginning of the 21st century, various chordoma cell lines and animal models have been reported, which have partially revealed the intrinsic mechanisms of tumor initiation and progression by next-generation sequencing (NGS) techniques. In the current review, we make a systematic overview of the chordoma models and related sequencing studies in a chronological manner, from the first patient-derived chordoma cell line U-CH1 to diversified pre-clinical models such as the patient-derived organoids-based xenograft (PDX) and patient-derived organoid (PDO) models. With the help of these modern sequencing techniques, mutations and expression signatures such as the expression of Brachyury and over activated receptor tyrosine kinases (RTKs) have been revealed and considered as potential treatment targets. With the help of computational and bioinformatics techniques, drug repositioning/repurposing and individualized high-throughput drug screening have been available. These advantages facilitate the research and development of comprehensive and personalized treatment strategies for indicated patients and will dramatically improve their prognoses in the near feature.